Identification of leaf rust genes in wheat varieties through sts markers (Bangladesh Journal of Botany, 2023)
Leaf rust caused by Puccinia triticinia is the most destructive disease which reduces wheat production. Thirty-eight wheat varieties were screened for four leaf rust resistance genes viz. Lr10, Lr26, Lr34 and Lr47 through STS markers. Among them Lr10 gene showed its presence in 16 genotypes, Lr26 in 8, both Lr34 and Lr47 in 10 each. Variety Anza+2ns showed promising results by the presence of three Lr genes (Lr10, Lr26 and Lr47) surely recommended for crop improvement and/or direct utility at farmers field. Chakwal-97, Indus-79, Marwat-Y-01, Mumal-2002, Khyber-83, Pasban-90, Pari-73, Lr-268, and Satluge-86 showed 2 genes presence while 23 with single gene and 5 without any response. A diagnostic band of size 310, 258, 1000 and 380-450 bps was amplified showing presence of Lr10, Lr34, Lr26 and Lr47. Marker STS are suggested for large scale germplasm screening during marker assisted breeding.Bangladesh J. Bot. 52(3): 709-714, 2023 (September)